THE SURVEY OF THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND ORGANIZATIONAL COMMITMENT AMONG ZAHEDAN MEDICAL SCIENCES UNIVERSITY STAFF IN 2016 Research Article - Miandoab, Nazanin Yousefian; SadeghZare; Salar, Ali Reza; Hossein Chalak, Mohammad; Jafari, Hossein (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Nowadays, human relationships with the organizations are among the most important issues and organizational problems which can direct the organization to the crash point. Emotional intelligence (EI) has extensively influenced the work-related behaviors such as teamwork, expansion of the talents, innovation, service providing quality, and customer loyalty and can lead to job satisfaction and organizational commitment. Therefore, according to the effects that EI can exert on the organizational commitment and productivity of the organization, the present study has been conducted with the objective of surveying the relationship between EI and organizational commitment. Methods: The present study is a cross-sectional descriptive-analytical research which has been conducted on 160 individuals from Zahedan Medical Sciences University staff who were selected based on a random method in 2016. To gather the information, a three-part questionnaire was applied the first part of which was connected to the demographic characteristics; the second part was related to the EI standard questionnaire; the third part was pertaining to the organizational commitment standard questionnaire. Data were analyzed by taking advantage of SPSS 19 and descriptive statistics, Pearson correlation, variance analysis, and independent t-test. Results: The results of the present study indicated that the individuals’ average age was 36.54Â±10.03, 98 individuals were women, 137 individuals were married. The individual’s total mean score in EI was 114.11Â±14.07 which has been reported to be high, according to the questionnaire ranking and the organizational commitment total mean score was 75.19Â±7.7. In the present study, the relationship between EI and organizational commitment was found to be statistically significant (p=0.005). Conclusion: The results obtained in the current study are consistent with the results obtained from the cited studies, and there was a significant relationship between EI and organizational commitment. Keywords: Organizational commitment, Emotional intelligence, University staff.